FISH analysis of PTEN in endometrial carcinoma. comparison with SNP arrays and MLPA - Maiques, Oscar (Histopathology, 2014)
AIMS: To check the usefulness of a standardized protocol of PTEN FISH in 31 endometrial carcinomas (ECs) in comparison with SNP array (SNPA), multiplex ligation-dependent probe amplification (MLPA), and immunohistochemistry. METHODS AND RESULTS: Fluorescence in-situ hybridization analysis showed two PTEN copies in 17 cases, three copies in nine cases, hemizygous deletion in two cases, and diverse cell populations with different PTEN copy number in three cases. A good correlation was seen between FISH and SNPA, particularly in cases with three copies. FISH identified two cases with entire deletion of chromosome 10, but did not identify a focal deletion of PTEN. Five cases with PTEN deletion and duplication of the second allele by SNPA were interpreted as normal by FISH. Concordance between FISH and MLPA was seen in 15 cases with two copies, and in two cases with PTEN deletion. Six cases were interpreted as amplified by MLPA, but showed polyploidy by FISH. FISH was superior to SNPA and MLPA in assessing the tumours with diverse cell populations with different PTEN copies. CONCLUSIONS: The results show good concordance between FISH, SNPA and MLPA. SNPA was superior in tumours with deletion of one copy and duplication of the second allele. FISH was superior in assessing tumour heterogeneity.